A criterion for the effect of parallel mode rotation on non- isothermal flow through square channel. (August 2019) - Hanafizadeh, Pedram; Karbalaee M., Sina; Attarpour, Rashidoddin; Ashjaee, Mehdi
Highlights: Centrifugal buoyancy is the main mechanism that governs the secondary flows induced by rotation. Rise in rotational speed doesn't necessarily result in increase in Nusselt number. A dimensionless group is introduced as a criterion to judge the rotational effects. The conditions in which the rotation positively affects the heat transfer is explored. Abstract: In this paper, turbulent airflow and heat transfer are studied numerically in a square sectioned channel which is rotating about a parallel axis. Channel rotation may create secondary flows as a result of centrifugal buoyancy and Coriolis forces which may increase the heat transfer coefficient and wall friction. Under certain conditions that the axial flow is dominant over the rotation, the effects of rotation can simply be ignored which means that friction factor and Nusselt number can be calculated regardless of rotation. This paper explores a novel criterion to demonstrate how the rotation affects the fluid flow and heat transfer. Rotational Grashof number ( Gr Ω ) and Reynolds number ( Re Ω ) are chosen to describe the rotation effects in addition to Reynolds number ( Re ) taking the axial flow into account. The results show that at a given Gr Ω and, Re Ω a specific Reynolds number ( Re ∗ ) in which the effects of rotation vanishes can be defined. It is revealed that Re ∗ may be presented as a function of Gr Ω only. With this regards, a non- dimensional group as Gr Ω a 1 / R e is obtained which is utilized to judge the rotational effects. It is shown that for Gr Ω a 1 / R e > 0.0167 the rotation starts to become important while for Gr Ω a 1 / R e < 0.0167 the Nusselt number is approximately equal to stationary counterpart.